2023
DOI: 10.2174/1573406418666220820110551
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights on Synthetic Methods and Pharmacological Potential in Relation with Structure of Benzothiazoles

Abstract: Benzothiazole is a bicyclic heterocyclic compound that contains benzene fused with 1, 3-thiazole ring. Several researches established the potential of benzothiazoles as important moiety in various adverse pharmacological conditions. Benzothiazole and its derivatives have been in use and marketed as anti-microbial, anti-inflammatory, anti-diabetic, anti-oxidant, anti-convulsant, anti-tumor, etc. The variations in pharmacological potentials of the benzothiazole and its derivatives have been in rational with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Various heterocyclic analogs of piperazine are synthesized and modified towards anticancer activity that acts against different cell lines such as MDA‐MB‐435, and HCT‐8, HL‐60, etc. (Yadav et al., 2023). Singh et al.…”
Section: Biological Activity and Structure–activity Relationship Of P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Various heterocyclic analogs of piperazine are synthesized and modified towards anticancer activity that acts against different cell lines such as MDA‐MB‐435, and HCT‐8, HL‐60, etc. (Yadav et al., 2023). Singh et al.…”
Section: Biological Activity and Structure–activity Relationship Of P...mentioning
confidence: 99%
“…Various heterocyclic analogs of piperazine are synthesized and modified towards anticancer activity that acts against different cell lines such as MDA-MB-435, and HCT-8, HL-60, etc. (Yadav et al, 2023). Singh et al reported a synthesis of two groups of piperazine salicylanilide derivatives 4-(3-(4-ethylpiperazin-1-yl)propoxy)-N-phenyl benzamide (77) and (4-(3-(4-ethylpiperazin-1-yl) propoxy) phenyl) (4-phenylpiperazin-1-yl) methanone (78).…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The benzothiazole core serves as a privileged building block of small molecule ligands endowed with a broad range of biological activities such as anti-inflammatory activity targeting a plethora of crucial enzymes including COXs [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The strategy of researching novel drug candidates with new mechanisms of action are also objective of our studies, and in recent years the benzothiazole nucleus has received much attention by the scientific community. Benzothiazole is a bicyclic heterocyclic compound, presenting a benzene ring fused to a five-membered ring comprising nitrogen and sulfur atoms, named thiazole (Singh et al, 2023;Yadav et al, 2023). This moiety is associated to a wide spectrum of biological activities, including antitubercular (Pinheiro et al, 2019), antibacterial (Kashyap et al, 2023), antiinflamatory (Sluter et al, 2023), anticonvulsant (Kyllo et al, 2023), antimalarial (Okonkwo et al, 2023), anthelmintic (Swaroopa et al, 2022), antileishmanial (Lasing et al, 2020), antidiabetic (Kousaxidis et al, 2023), antidepressant (Liu et al, 2022), and antitumor agents (Huang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%